Wearable solid-state capacitors based on two-dimensional material all-textile heterostructures. Issue 20 (8th May 2019) - Qiang, Siyu; Carey, Tian; Arbab, Adrees; Song, Weihua; Wang, Chaoxia; Torrisi, Felice
Abstract : Two dimensional (2D) materials are a rapidly growing area of interest for wearable electronics, due to their flexible and unique electrical properties. Abstract : Two-dimensional (2D) materials are a rapidly growing area of interest for wearable electronics, due to their flexible and unique electrical properties. All-textile-based wearable electronic components are key to enable future wearable electronics. Single component electrical elements have been demonstrated; however heterostructure-based assemblies, combining electrically conductive and dielectric textiles such as all-textile capacitors are currently missing. Here we demonstrate a superhydrophobic conducting fabric with a sheet resistance R s ∼ 2.16 kΩ □ −1, and a pinhole-free dielectric fabric with a relative permittivity ε r ∼ 2.35 enabled by graphene and hexagonal boron nitride inks, respectively. The different fabrics are then integrated to engineer the first example of an all-textile-based capacitive heterostructure with an effective capacitance C ∼ 26 pF cm −2 and a flexibility of ∼1 cm bending radius. The capacitor sustains 20 cycles of repeated washing and more than 100 cycles of repeated bending. Finally, an AC low-pass filter with a cut-off frequency of ∼15 kHz is integrated by combining the conductive polyester and the capacitor. These results pave the way toward all-textile vertically integrated electronic devices.